2019
DOI: 10.1200/jco.18.01600
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax Combined With Low-Dose Cytarabine for Previously Untreated Patients With Acute Myeloid Leukemia: Results From a Phase Ib/II Study

Abstract: PURPOSE Effective treatment options are limited for patients with acute myeloid leukemia (AML) who cannot tolerate intensive chemotherapy. An international phase Ib/II study evaluated the safety and preliminary efficacy of venetoclax, a selective B-cell leukemia/lymphoma-2 inhibitor, together with low-dose cytarabine (LDAC) in older adults with AML. PATIENTS AND METHODS Adults 60 years or older with previously untreated AML ineligible for intensive chemotherapy were enrolled. Prior treatment of myelodysplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
503
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 538 publications
(526 citation statements)
references
References 38 publications
(41 reference statements)
17
503
4
2
Order By: Relevance
“…12 These findings prompted evaluation of venetoclax in combination with an HMA (azacitidine or decitabine; NCT02203773) or LDAC (NCT02287233) in patients 65 years of age or older newly diagnosed with AML and not eligible for standard induction therapy. Results from these studies 13,14 demonstrated that the combination of venetoclax with an HMA or LDAC leads to higher overall response rates (ORRs) than those reported for either LDAC or HMA alone. Both combinations were granted breakthrough designations and were approved by the United States Food and Drug Administration (FDA) under accelerated approval pathway.…”
Section: Introductionmentioning
confidence: 99%
“…12 These findings prompted evaluation of venetoclax in combination with an HMA (azacitidine or decitabine; NCT02203773) or LDAC (NCT02287233) in patients 65 years of age or older newly diagnosed with AML and not eligible for standard induction therapy. Results from these studies 13,14 demonstrated that the combination of venetoclax with an HMA or LDAC leads to higher overall response rates (ORRs) than those reported for either LDAC or HMA alone. Both combinations were granted breakthrough designations and were approved by the United States Food and Drug Administration (FDA) under accelerated approval pathway.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to its cancer relevance, another interesting miR-16 target that has been established is the anti-apoptotic protein Bcl2 (40). Bcl2 inhibitors are currently being introduced as potential therapeutic tools in AML (41), and interestingly, a synergy between venetoclax and the FLT3-inihibitor quizartinib has been described (42). It would be interesting to establish whether miR-16-dependent regulation of Bcl2 is involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 145 patients, venetoclax plus azacitidine or decitabine produced a CR/CRi in 67%, median OS lasting 17.5 months and 46% were alive at 2 years . Similarly, in study of 82 patients (prior HMA exposure allowed), venetoclax plus LDAC (20 mg/m 2 subcutaneous daily d1‐10) produced a CR/CRi in 54%, median OS lasting 10.1 months and 44% were alive at 1 year . Importantly, responses were achieved rapidly (median ~1 month), with virtually no clinical tumor lysis syndrome and low early (30‐day) mortality (3%‐6%).…”
Section: Challenging the Notion That Treating Older Patients With Amlmentioning
confidence: 97%
“…64 In clinical studies, although the selective BCL-2 inhibitor venetoclax has modest activity as monotherapy in R/R AML, 65 were alive at 1 year. 67 Importantly, responses were achieved rapidly 82 This is a promising preliminary efficacy in elderly AML despite the lack of superiority of combination therapy over azacitidine alone in higher-risk MDS. 83 A phase 3 randomized study of pracinostat (or placebo) in combination with azacitidine is currently underway in patients unfit for standard induction chemotherapy (NCT03151408).…”
Section: The Rise Of the Bh3-mimeticsmentioning
confidence: 99%